2019
DOI: 10.1007/978-3-030-11509-8_17
|View full text |Cite
|
Sign up to set email alerts
|

The Balanced Connected Subgraph Problem

Abstract: The problem of computing induced subgraphs that satisfy some specified restrictions arises in various applications of graph algorithms and has been well studied. In this paper, we consider the following Balanced Connected Subgraph (shortly, BCS) problem. The input is a graph G = (V, E), with each vertex in the set V having an assigned color, "red" or "blue". We seek a maximum-cardinality subset V ′ ⊆ V of vertices that is color-balanced (having exactly |V ′ |/2 red nodes and |V ′ |/2 blue nodes), such that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…This section is devoted to showing that BCS can be solved in O(n 2 ) time for trees, which improves upon the previous running time O(n 3 ) of [3]. We also give an algorithm for BCS on bounded treewidth graphs whose running time is O(n 2 ) as well.…”
Section: Trees and Bounded Treewidth Graphsmentioning
confidence: 83%
See 3 more Smart Citations
“…This section is devoted to showing that BCS can be solved in O(n 2 ) time for trees, which improves upon the previous running time O(n 3 ) of [3]. We also give an algorithm for BCS on bounded treewidth graphs whose running time is O(n 2 ) as well.…”
Section: Trees and Bounded Treewidth Graphsmentioning
confidence: 83%
“…The essential idea behind our algorithm is the same as one in [3]. Let T be a bicolored rooted tree.…”
Section: Trees and Bounded Treewidth Graphsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we study the BCS problem on unit-disk graphs. It has been shown that this problem is NP-hard on planar graphs [2]. Besides, we know that every planar graph can be represented as a disk graph (due to Koebe's kissing disk embedding theorem [9]).…”
Section: Unit Disk Graphsmentioning
confidence: 99%